ANALISIS INVESTASI DAN PERTUMBUHAN EKONOMI DI INDONESIA - Selly Prima Desweni (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2017)
This study aims to analyze (1) the effect of interest rates, inflation and economic growth toinvestment in Indonesia, (2) the effect of consumption, investment, government expenditure and netexports to economic growth in Indonesia. This type of research is descriptive and associativeresearch is research that describes the research variables and find whether there is influencebetween independent variables and the dependent variable. The type of data in this research issecondary data from the years 1995-2015 with the techniques of data collection documentation.Analysis of the data used are: simultaneous analysis, the data distribution normality test,autocorrelation, and heterokedastisitas, testing the hypothesis with α 5%. The results of the studyare (1) the interest rate a significant negative effect on investment in Indonesia (sig = 0.0293<0.05), (2) inflation a significant negative effect on investment in Indonesia (sig = 0.000 <0.05);(3) economic growth is positive and significant effect on investment in Indonesia (sig = 0.000>0.05), (4) consumption a significant positive effect on economic growth in Indonesia (sig = 0.0000<0.05), (5 ) investment positive and significant effect on economic growth in Indonesia (0.0101<0.05), (6) government expenditure and significant positive effect on economic growth inIndonesia (sig = 0.0175 <0.05), (7) net exports are not positive and significant impact oneconomic growth in Indonesia (sig = 0.1815> 0.05.The proposed recommendation in this research is expected the Government should payattention and increase total investment in Indonesia, maintain the stability conditions of theIndonesian economy, exercise control over interest rates and inflation in Indonesia in order toincrease the investors to invest in Indonesia, in addition, the government also needs to createpolicies in enhancing the role of all sectors of the economy such as consumption, investment,government expenditure and net exports were a major sector in improving the economy andeconomic growth in IndonesiaKeyword : interest rrates, inflatio